2020
DOI: 10.1159/000506164
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Nonsynchronized Nasal Intermittent Positive Pressure Ventilation versus Nasal CPAP after Extubation of VLBW Infants

Abstract: Background and Objectives: Nasal continuous positive airway pressure (NCPAP) is a useful method of respiratory support after extubation. However, some infants fail despite CPAP use and require reintubation. Some evidence suggests that synchronized nasal intermittent positive pressure ventilation (NIPPV) may decrease extubation failure in preterm infants. Nonsynchronized NIPPV (NS-NIPPV) is being widely used in preterm infants without conclusive evidence of its benefits and side effects. Our aim was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…NIPPV also has advantages in reducing the oxygen inhalation time and the incidence of BPD. Another recent RCT ( 17 ) showed that NIPPV and NCPAP had similar effects on neonatal RDS; there was no reported difference in the incidence of intubation, BPD, and mortality between the NIPPV and NCPAP groups. Moreover, there was also no difference in the incidence of intraventricular hemorrhage, pneumothorax, and invasive ventilation time between the two groups.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…NIPPV also has advantages in reducing the oxygen inhalation time and the incidence of BPD. Another recent RCT ( 17 ) showed that NIPPV and NCPAP had similar effects on neonatal RDS; there was no reported difference in the incidence of intubation, BPD, and mortality between the NIPPV and NCPAP groups. Moreover, there was also no difference in the incidence of intraventricular hemorrhage, pneumothorax, and invasive ventilation time between the two groups.…”
Section: Discussionmentioning
confidence: 96%
“…We retrieved 1,867 literatures from the database, and finally selected 10 literatures for study (15)(16)(17)(20)(21)(22)(23)(24)(25)(26). The 10 literatures included 1,104 patients, 557 in the NIPPV group and 547 in the NCPAP group.…”
Section: Characteristics Of Included Literaturementioning
confidence: 99%
See 1 more Smart Citation